The Role of Migrant Parents in Forming Students' Religious Attitudes at MTs. An-Najah I Karduluk, Pragaan District, Sumenep Regency in 2025 - Syifa’ Nuril Mushthafiyah; Abd. Qadir Jailani (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
The role as a parent is the responsibility and obligation carried out by parents towards their children, namely in educating and forming the child’s character and attitude to be religious. Religious attitude is a form of achievement that a child must have, namely having good character, polite and courteous morals, and worship with devotion to the Almighty Creator.The aim of this research is to describe the role of overseas parents in shaping students’ religious attitudes and the supporting and inhibiting factors even when they are migrating. This research uses descriptive qualitative methods. The data sources in this research are overseas parents, homeroom teachers, school teachers and MTs Students An-Najah I Karduluk. Data collection using interviews, observation and documentation. The results of this research show that the role of overseas parents in forming students’ religious attitudes is, (1) Instilling good behavior in children from an early age (2) Getting children used to discipline regarding time, such as worship, playing and studying (3) Providing guidance every time regarding etiquette towards other people, especially older people. Meanwhile, the supporting factors consist of substitute families, parents, teachers and Islamic boarding school institutions. Meanwhile, inhibiting factors consist of the environmen, distance and time with overseas parents and factors within the child himself.